PENGARUH METODE EXAMPLE NON EXAMPLE TERHAAP HASIL BELAJAR SISWA DI SMP ISLAM MA’ARIF 02 KOTA MALANG - Alifatus Zufi; Ika Ratih Sulistiani; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
A teacher in delivering material should choose a teaching method that is appropriate to the class situation or students so that students feel interested in following the lessons being taught. For example, non-examples teaching methods are teaching methods that use pictures as a medium of learning. This study aims to determine the effect of the example non example method on student learning outcomes at SMP Islam Ma'arif 02 Malang. This research method uses a quantitative approach to the type of experiment (experimental study). Data collection techniques in this study using tests. Learning outcomes after the application of the non-example method obtained a good score, and there was a significant effect of the non-example method on student learning outcomes as evidenced by the results of hypothesis testing using paired sample testing indicating that the sig (2-tail) value is less than 0 .05 is 0.000 (0.000 < 0.05) and states that Ho is rejected and Ha is accepted.